Manganese-Doped Cerium Oxide Nanocomposite Induced Photodynamic Therapy in MCF-7 Cancer Cells and Antibacterial Activity. (25th September 2019) - Atif, M.; Iqbal, Seemab; Fakhar-E-Alam, M.; Ismail, M.; Mansoor, Qaisar; Mughal, Lubna; Aziz, Muhammad Hammad; Hanif, Atif; Farooq, W. A.
Abstract : In this experimental approach, we explored the structures, morphologies, phototoxicities, and antibacterial activities of undoped and Mn-doped ceria nanocomposite materials, Mn x Ce1− x O2. The Mn x Ce1− x O2 nanocomposites were synthesized by employing a soft chemical route. Our prime focus was on the influence of different factors, both physical and chemical, i.e., the concentration of manganese in the product, size of the nanocomposite, drug dose, and incubation time, on the bacterial strains. Different bacterial strains were selected as experimental biological models of the antibacterial activity of the manganese-doped cerium oxide nanocomposite. In addition to the photodynamic response, the adenocarcinoma cell line (MCF-7) was also studied. Based on cell viability losses and bacterial inhibition analyses, the precise mechanisms of apoptosis or necrosis of 5-ALA/PpIX-exposed MCF-7 cells under 630 nm red lights and under dark conditions were elucidated. It was observed that the undoped nanocomposites had lower cytotoxicities and inhibitions compared with those of the doped nanocomposites towards pathogens. The antibacterial activity and effectiveness for photodynamic therapy were enhanced in the presence of the manganese-doped ceria nanocomposite, which could be attributed to the correlation of the maximum reactive oxygen species generation for targeted toxicity and maximum antioxidant property in bacteria growth inhibition. The optimized cell viability dose and doping concentration will be beneficial for treating cancer and bacterial infections in the future.